2022
DOI: 10.3389/fcvm.2022.1013501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of C-reactive protein as predictor of adverse prognosis in acute myocardial infarction after percutaneous coronary intervention: A systematic review and meta-analysis from 18,715 individuals

Abstract: BackgroundProper prognostic biomarker is of great importance for clinical decision-making in patients with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI). Although recently emerges plenty of novel inflammatory biomarkers, the canonical inflammatory mediator C-reactive protein still plays an important role in prognosing adverse post-infarction complications.MethodsPubMed, Embase, and Medline were systematically searched from the establishment of databases up to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Previous observational studies have found many peripheral inflammatory factors and inflammatory cells associated with AMI. Liu et al reported that C-reactive protein (CRP) may be a prospective predictor of prognosis in patients with AMI undergoing percutaneous coronary intervention [ 6 ]. Several studies suggested that interleukin (IL)-1, IL-6 and IL-18 were associated with the onset of AMI, myocardial repair, the development of complications, and the readmission of patients to the hospital, whereas IL-10 may be antagonistic to IL-6 in this disease [ 7 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous observational studies have found many peripheral inflammatory factors and inflammatory cells associated with AMI. Liu et al reported that C-reactive protein (CRP) may be a prospective predictor of prognosis in patients with AMI undergoing percutaneous coronary intervention [ 6 ]. Several studies suggested that interleukin (IL)-1, IL-6 and IL-18 were associated with the onset of AMI, myocardial repair, the development of complications, and the readmission of patients to the hospital, whereas IL-10 may be antagonistic to IL-6 in this disease [ 7 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the risk stratification of those patients, different inflammatory and hematological markers have been tested as predictive factors for MACEs after NSTEMI and STEMI. Among inflammatory markers, elevated C-reactive protein (CRP) has been proven to be the strongest independent factor in predicting overall lethal outcome, cardiac death, and MACEs in STEMI or NSTEMI patients after percutaneous coronary intervention (PCI) [ 1 ]. Platelets, as very important factors, are involved in the mechanisms of the development of cardiovascular diseases, such as atherosclerosis and ACS.…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients with AMI would have adverse events including stent thrombosis, acute heart failure, and sudden cardiac death even after the development of PCI and GDMT [3,4]. Several clinical factors are reported to be related to poor long-term prognosis in patients with AMI [5][6][7]. However, predictors for long-term outcomes of AMI are still important for stratifying patients with AMI according to the future risk after discharge.…”
Section: Introductionmentioning
confidence: 99%